PENGEMBANGAN MODEL KONTEKSTUAL BERBASIS ETNO PACU JALUR (MKEPJ) DI SEKOLAH DASAR - Erlisnawati Erlisnawati; Jesi Alexander Alim; Hendri Marhadi; Eddy Noviana; Bedriati Ibrahim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study was intended to construct Pacu Jalur ethnic-based contextual model, a learning model developed based on the stages of Pacu Jalur Ethno. This study was a research and development (R&D) study using Borg & Gall stages. This study was developed until the product development stage, which was developing a learning model based on Pacu Jalur Ethno. Then, the product was validated by experts to know the appropriateness of the Pacu Jalur Ethno- based contextual model used in learning. The data were collected by literature review, interviewing, observation, and documentation. Based on the result of the study, Pacu Jalur Ethno based contextual model was appropriate to be implemented in the learning process by using the following syntax: stage 1, planning (merencanakan); stage 2, doing the tasks (membuek jalur); stage 3, discussion (bapacu); and stage 4, closing (panutuik). Pacu Jalur's ethnic-based contextual model described that learning activities could apply local wisdom in the current place where the learning was carried out. Therefore, the learning activities became more concrete since they connected the concept with students’ daily life.